2017
DOI: 10.3390/ijms18122765
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Down-Regulation of Barley Lipoxygenase LOX2.2 Affects Jasmonate-Regulated Genes and Aphid Fecundity

Abstract: Aphids are pests on many crops and depend on plant phloem sap as their food source. In an attempt to find factors improving plant resistance against aphids, we studied the effects of overexpression and down-regulation of the lipoxygenase gene LOX2.2 in barley (Hordeum vulgare L.) on the performance of two aphid species. A specialist, bird cherry-oat aphid (Rhopalosiphum padi L.) and a generalist, green peach aphid (Myzus persicae Sulzer) were studied. LOX2.2 overexpressing lines showed up-regulation of some ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Both the JA and salicylic acid pathways can respond to the invasion of pathogenic bacteria, and these two pathways show synergistic effects [51]. Many previous studies have shown that LOX genes are regulated by jasmonic acid and other hormones in species, such as A. thaliana, H.vulgare and C. jubata [52][53][54]. These reports also support the possible role of LOX genes in the defense mechanism of Tartary buckwheat.…”
Section: Analysis Of Cis-elements In Promoters Of Ftlox Genessupporting
confidence: 62%
“…Both the JA and salicylic acid pathways can respond to the invasion of pathogenic bacteria, and these two pathways show synergistic effects [51]. Many previous studies have shown that LOX genes are regulated by jasmonic acid and other hormones in species, such as A. thaliana, H.vulgare and C. jubata [52][53][54]. These reports also support the possible role of LOX genes in the defense mechanism of Tartary buckwheat.…”
Section: Analysis Of Cis-elements In Promoters Of Ftlox Genessupporting
confidence: 62%
“…Silencing of OsHI‐LOX or Na‐LOX3 in rice and tobacco, respectively, interfered with the induction of JA upon herbivore feeding (Halitschke and Baldwin ; Zhou et al ; Lu et al ). Likewise, in a recent study in barley, overexpression and downregulation of LOX2.2 affected the expression of JA‐related genes depicting its role in JA‐biosynthesis (Losvik et al ).…”
Section: Discussionmentioning
confidence: 91%
“…cultivar Otis (Marimuthu and Smith, 2012). Furthermore, overexpression of HvLOX2 in barley resulted in decreased R. padi fecundity (Losvik et al, 2017), pointing to a functional role of this gene and JA signalling in short-term barley defence against aphids. Expression levels of CmERF1 in early responses (6h) to aphid infestation were around ten-fold higher in a resistant variety of melon compared with a susceptible variety (Anstead et al, 2010), and higher ET levels have been reported to contribute to R. maidis resistance in maize (Louis et al, 2015).…”
Section: Contribution Of Defensive Thionins and Multiple Phytohormonementioning
confidence: 94%
“…include increased expression of thionin (antimicrobial peptides) genes (Delp et al, 2009;Mehrabi et al, 2014;Escudero-Martinez et al, 2017), increased chitinase and β-1,3-glucanase activity (Forslund et al, 2000), and the presence of plant secondary metabolites (Gianoli and Niemeyer, 1998). Plant phythormone signalling pathways, including Abscisic Acid (ABA), Salicylic Acid (SA), Jasmonic Acid (JA) and Ethylene (ET) signalling, mediate coordinated molecular responses to herbivory via the regulation of defence signalling genes and the biosynthesis of defensive allelochemicals (Smith and Boyko, 2007;Bari and Jones, 2009;Morkunas et al, 2011;Foyer et al, 2016); higher constitutive expression of phytohormone signalling genes can lead to improved resistance against aphids in cereals (Losvik et al, 2017). With a lack of full resistance, especially in cereal crops, the use of partial-resistances to provide crop protection is a powerful approach (Broekgaarden et al, 2011;Dempewolf et al, 2014).…”
Section: Tablesmentioning
confidence: 99%